Design and fabrication of thermoplastic elastomer with ionic network: A strategy for good performance and shape memory capability. (3rd May 2021) - Salaeh, Subhan; Das, Amit; Wießner, Sven
Abstract: Smart elastomeric materials with outstanding performance and multifunctional properties are highly desirable for many potential applications. Here, strong shape memory materials were prepared based on poly(vinylidene fluoride)/carboxylated nitrile butadiene rubber (PVDF/XNBR) blends containing ionic crosslinks. The ionic clusters in the blends improved mechanical properties and elasticity of the shape memory blends. Interestingly, the elongation at break of this blend increased with rubber content without deterioration of tensile strength. A remarkable improvement of mechanical performance of the blends arose from the reinforcing cite and dynamic mobility of ionic clusters in XNBR matrix. The combination of blending and ionic cross-linking not only improved mechanical properties but also improved shape memory performance. The blends prepared in this work exhibited thermally triggered shape memory because both phases are responsible for shape fixity and recovery. As a consequence, the blends with high XNBR content showed high shape recovery (90%). Finally, this work provides an efficient approach to design new ionic crosslinked blends with excellent mechanical properties and shape memory properties. Graphical abstract: Image 1 Highlights: PVDF/XNBR blends induced by ionic cross-links were developed and characterized for the first time. Incorporation of ZnO into PVDF/XNBR blends improved mechanical properties and viscoelastic properties. Ionic cross-linked blends result in high-speed shape recovery behavior and showed excellent shape memory properties. The first report to demonstrate shape memory performance of ionically cured PVDF/XNBR blend.